Pengaruh Komunikasi Organisasi Dan Motivasi Kerja Terhadap Kinerja Karyawan Pada Saat Pandemi Covid-19 Di Wilayah PT PLN (Persero) UPT Probolinggo - Oktavia Dwi Ambarwati; Muhammad Ridwan Basalamah; Nurhidayah Nurhidayah (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract This study aims to examine the effect of organizational communication and motivation on the performance of employees of PT PLN (Persero) UPT Probolinggo. The Covid-19 pandemic has had many impacts in various fields, including organizational communication and work motivation within the company. PT PLN (Persero) UPT Probolinggo routinely carries out activities called CoC (Code of Conduct), and since then there has been an increase in performance values in the UPT Probolinggo area. Where the CoC activities reflect organizational communication and work motivation. The method used in this research is quantitative descriptive analysis method and statistical analysis method using Multiple Regression Test. The results of this study indicate a significant influence of organizational communication and motivation on employee performance either partially or simultaneously. Keywords: Organizational Communication, Motivation, Employee Performance, PT PLN (Persero) UPT Probolinggo